Answer:
For 1 cup of peanut Kevin will use
of raisins.
Explanation:
Given:
cups of peanuts =
cups of raisin
can be rewritten as
cups of peanuts =
cups of raisin
We need to find number of cups of raisins used in 1 cup of peanut.
Solution:
Now we know that;
cups of peanuts =
cups of raisin
So 1 cup of peanut = number of cups of raisins used in 1 cup of peanut
Now by using Unitary method we get;
number of cups of raisins used in 1 cup of peanut =
![((9)/(4))/((1)/(2))=(9)/(4)* (2)/(1) = (9)/(2) \ cup \ \ \ OR \ \ \ 4(1)/(2) \ cup](https://img.qammunity.org/2021/formulas/mathematics/high-school/ozeqgiu47pury89qwxpu0h8035vtrtandv.png)
Hence For 1 cup of peanut Kevin will use
of raisins.